Peripheral Ossifying Fibroma of the Posterior Maxilla: A Case Report - S., Mithula Nair; Ajila, Vidya; Hegde, Shruthi; Babu, G. Subhas; Ghosh, Rumela (Journal of Health and Allied Sciences NU, 2016)
Peripheral ossifying fibroma (POF) is a reactive lesion usually arising from the interdental gingiva. The etiology is considered to be secondary to trauma or other local irritating factors. POF is almost always confused with pyogenic granuloma and peripheral giant cell granuloma. It usually shows a predominance of incidence in anterior region of maxilla and among females. Lesions are rarely larger than 2 cms in size. Incidence of peripheral ossifying fibroma in the posterior maxilla is also rare. Here we report a large peripheral ossifying fibroma occurring in a 40 year old man in the posterior maxillary region which had extended to the occlusal surface of the third molar region causing pain and erythema.
Keywords: Peripheral ossifying fibroma; Gingiva; Maxilla